Alcohol misuse to down-regulate positive emotions: A cross-sectional multiple mediator analysis among US military veterans. (June 2020) - Weiss, Nicole H.; Forkus, Shannon R.; Raudales, Alexa M.; Schick, Melissa R.; Contractor, Ateka A.
Highlights: More severe PTSD symptoms were related to greater alcohol misuse. PTSD was indirectly related to alcohol misuse through positive emotional avoidance. Positive emotional intensity did not explain the PTSD to alcohol misuse relation. Positive emotional intensity and positive emotional avoidance were sequential mediators. Targeting positive emotional avoidance may reduce the PTSD-alcohol misuse relation. Abstract: Introduction: The co-occurrence of posttraumatic stress disorder (PTSD) and alcohol misuse presents a pervasive and clinically relevant concern among US military veterans. Objective: The current investigation sought to examine the role of positive emotion dysfunction in the relation between PTSD symptomatology and alcohol misuse. To do so, we examined the separate and sequential roles of positive emotional intensity and positive emotional avoidance in the relation between PTSD symptoms and alcohol misuse among US military veterans. Method: Cross-sectional data were collected from 468 US military veterans ( M age = 37.74, 70.5% male, 69.0% White) who responded to an online survey. Results: Findings suggest that positive emotional avoidance, separately, and positive emotional intensity and positive emotional avoidance, sequentially, mediated the relation between PTSD symptoms and alcohol misuse. Conclusions: Findings advance theory on the role of positive emotions and related processes in the co-occurrence of PTSD and alcohol misuse, and highlight important avenues for future research and treatment focused on the PTSD-alcohol misuse co-occurrence.